O discurso do uso didático da imagem virtual na escola - Maciel, Maria do Rosário Gomes Germano (2020)
The study on the didactic usage of the virtual image discourse at school inserts itself in the recurrent discussions about the presence of the visual image in contemporary society and the usage of technological digital tools in the scholar institution. For that came, understandings on the potential visual imagetic amplify, in a general manner and a particular way of the virtual imagetic cultural artifact as resources that access it, articulate and produce pedagogical practices that mediate the knowledge at school. From the above, we have assumed the thesis that in the order of the discourse of contemporary society‘s visual culture the virtual image is constituted in a didactic-pedagogical device mediator of the knowledge at school. We have defined, as the investigation‘s general objective, analyze and describe the discourse on the didactic usage of virtual image at school. For that, we have leaned on the theoreticalmethodological fundaments of the Archeological Discourse Analysis from Michael Foucault (2015). We have carried out a survey of scientific works published in the period between 2001 and 2017, registered in the thesis bank of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) [Coordination for the Improvement of Higher Education Personnel] and Biblioteca Digital Brasileira de Teses e Dissertações (BDTD) [Brazilian Digital Library of Thesis and Dissertations], that treat of knowledge related to the didactic usage of virtual image at school. We have identified a significant number of productions related to the investigated subject. Posteriorly, we have mapped the discourse‘s web of signifier and signified of the didactic usage of virtual image at school in order to explicit the way the written things on the virtual image usage at school are meant. In this digging, we have found three discursive orders: the Info Educational Policy, the Didactic-Pedagogical and the Technological Virtual Imagetic. On the first one, we have identified the computer at school rule triggering policies, programs that give status to the creation of a National Policy for Educational Informatics, happening that mobilizes the informatization of public schools, the process of teachers‘ formation and Brazil‘s technological, economic and social inclusion discourse. On the second one, we have localized the virtual image with the enunciative function of mediating the comprehension of school subjects and foment the production of thinking, creativity and the liberty for the students to create ideas and analyze them. It also reveals to trigger the observation, the interaction, the participation, and the autonomy in the construction and reconstruction of school knowledge. On the last order, we have identified the Info Mathematical domain and the rule to the culture of virtuality and the internet correlates, digital language and hypertext.